The Effect of Dietary Protein Intake on the Risk of Gestational Diabetes. (14th December 2022) - Chen, Lingling; Du, Shuli; Song, Honghua; Chen, Jing; Lv, Cuiting; Li, Chunhui
Abstract : Background . The results of epidemiological studies on the association between dietary protein intake and gestational diabetes mellitus (GDM) are controversial. Thus, this systematic review and meta-analysis of cohort studies were established to attain comprehensive findings regarding the association between dietary protein and the risk of GDM. Methods . Bibliographic databases including PubMed, Scopus, Web of Science, and Google Scholar were searched to discover papers related to dietary protein and the risk of GDM. The summary relative risks with 95% confidence intervals (CIs) were estimated through a random effect model for the analysis of the highest versus the lowest categories of dietary proteins. Results . A significantly increased risk of GDM among women who consumed the highest amount of animal protein was observed (summarized risk estimate: 1.52; 95% CI: 1.07, 2.17; I 2  = 50.8%). No significant associations were identified regarding vegetable protein (summarized risk estimate:0.99, 95% CI: 0.80 to 1.23, I 2  = 63.8%) and total protein (summarized risk estimate: 1.12; 95% CI: 0.88, 1.41; I 2  = 35.4%). Conclusion . This review revealed that total protein intake had no relationship with the risk of GDM, while animal protein increases this risk. Further larger prospective cohort studies are required to confirm our results.